A Family of P Systems for Solving Linear Equations. Issue 4 (1st July 2017) - Guo, Ping; Wei, Lijiao; Chen, Haizhu; Liu, Ran
Abstract : Solving linear equations is one of the fundamental problems in numerical calculation and has a wide application in many science and engineering fields. We present a family of P systems to solve linear equations in which the coefficients are real numbers. An instance is given to illustrate the feasibility and effectiveness of our designed P systems. Our work contributes to make P systems to solve more complicated computation problems effectively.